New Mythological Figures in Spanish Cinema Dissident Bodies under Franco - Feenstra, Pietsie (Film Culture in Transition, 2011)
After General Francisco Franco died in 1975, Spanish cinema was bursting at the seams. Many film directors broke free from the ancient taboos which had reigned under Franco's dictatorship, introducing characters who transgressed the traditional borders of social, cultural, and sexual identities. The women, homosexuals, transsexuals, and delinquents who were considered lost, dissonant bodies under Franco's rule became the new protagonists of Spanish cinema. "Here is a 'book of passion' on the metamorphoses of post-Francoist Spain as it catapulted into the contemporary world (1975-95). It is a book that questions the power of myths expressed through passionate bodies, in particular bodies who for too long were marginalized in traditional societies." -Michèle Lagny, Université de Sorbonne Nouvelle Paris III